2010
DOI: 10.2214/ajr.10.4683
|View full text |Cite
|
Sign up to set email alerts
|

Shoulder MRI: What Do We Miss?

Abstract: Although MRI is an excellent tool for detecting some abormalities, there are a number of subtler abnormalities of clinical significance that give radiologists greater difficulty. By understanding the reasons for limited detection and modifying protocols accordingly, radiologists may be able to improve identification, allowing more accurate clinical decision making.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
13
0
1

Year Published

2012
2012
2015
2015

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 34 publications
(15 citation statements)
references
References 35 publications
(93 reference statements)
1
13
0
1
Order By: Relevance
“…Of the standard imaging planes, the oblique sagittal plane is thought to provide the best view of the coracohumeral ligament and superior glenohumeral ligament and their relationship with the LHB tendon as they traverse the rotator interval portion of the joint [17]. Prior studies have shown greater success at visualizing the biceps pulley components when the joint is distended with contrast agent, such as in the setting of MR arthrography [17,[26][27][28][29], but even with that advantage, small structures such as the superior glenohumeral ligament are often difficult to evaluate. Many patients with shoulder pain are imaged with the shoulder positioned in internal rotation because of comfort; this position crowds the soft tissues at the anterior aspect of the joint, making it even more difficult to distinguish the individual structures in this region [17].…”
Section: Biceps Pulley and Associated Injuriesmentioning
confidence: 99%
See 1 more Smart Citation
“…Of the standard imaging planes, the oblique sagittal plane is thought to provide the best view of the coracohumeral ligament and superior glenohumeral ligament and their relationship with the LHB tendon as they traverse the rotator interval portion of the joint [17]. Prior studies have shown greater success at visualizing the biceps pulley components when the joint is distended with contrast agent, such as in the setting of MR arthrography [17,[26][27][28][29], but even with that advantage, small structures such as the superior glenohumeral ligament are often difficult to evaluate. Many patients with shoulder pain are imaged with the shoulder positioned in internal rotation because of comfort; this position crowds the soft tissues at the anterior aspect of the joint, making it even more difficult to distinguish the individual structures in this region [17].…”
Section: Biceps Pulley and Associated Injuriesmentioning
confidence: 99%
“…Although the extraarticular LHB tendon is well seen and easily evaluated on axial images, the oblique course of the intraarticular LHB tendon makes it more difficult to inspect, especially as it exits the joint and enters the intertubercular groove. It is imperative to follow the intraarticular course of the LHB tendon on both oblique sagittal and oblique coronal imaging planes to detect subtle regions of caliber change or intrinsic signal abnormality that may indicate tendinosis or partial-thickness tears [29] (Fig. 7).…”
Section: Vinson Et Almentioning
confidence: 99%
“…But Applegate's study only included a few patients and only looked at the biceps' attachment area [11], while the current study look at the entire horizontal segment of the biceps. To our knowledge, no radiological studies have been performed specifically to look at the long portion of the biceps [12]. Based on the findings of the current study, CT arthrography seems to be the most relevant imaging modality to detect tendinopathy in the intra-articular portion of the long head of biceps.…”
Section: Discussionmentioning
confidence: 72%
“…Insgesamt sind diese Veränderungen jedoch wenig sensitiv und spezifisch. Ein Grund hierfür ist die relativ geringe Signalintensität von narbigem Kapselgewebe in fettsupprimierten Sequenzen [16].…”
Section: Magnetresonanztomographieunclassified